Adipose-derived stem cells attenuate pulmonary arterial hypertension and ameliorate pulmonary arterial remodeling in monocrotaline-induced pulmonary hypertensive rats. (April 2015) - Luo, Li; Lin, Taijie; Zheng, Suli; Xie, Zhenguo; Chen, Ming; Lian, Guili; Xu, Changsheng; Wang, Huajun; Xie, Liangdi
Abstract We investigated the effect of adipose-derived stem cells (ADSCs) transplantation effects on structural remodeling and pulmonary artery pressure in monocrotaline (MCT)-induced pulmonary hypertensive rats. In the first experiment, 32 male Sprague-Dawley (SD) rats were randomly divided into four groups (n = 8/group): 3 ADSCs treated groups and normal control (Ctrl). ADSCs were administered through the left jugular vein at 105, 106 and 107 cells, respectively, and a cell density of 106cells/ml was shown to be optimal. The GFP-tagged ADSCs were identified in the lungs and differentiated into endothelial-like cells. In the second experiment, 96 male SD rats were randomly divided into three groups (n = 32/group): Ctrl, MCT-induced pulmonary arterial hypertension (PAH), and PAH treated with ADSCs (ADSCs). Two weeks post-MCT administration, the ADSCs group received 1 × 106 ADSCs via the external jugular vein. Compared to PAH rats, mean pulmonary arterial pressure was decreased in rats at 1, 2, and 3 weeks after ADSCs-treatment (18.63 ± 2.15 mmHg versus 24.53 ± 2.90 mmHg; 23.07 ± 2.84 mmHg versus 33.18 ± 2.30 mmHg; 22.98 ± 2.34 mmHg versus 36.38 ± 3.28 mmHg, p < 0.05). Meanwhile, the right heart hypertrophy index (36.2 1 ± 4.27% versus 41.01 ± 1.29%; 39.47 ± 4.02% versus 48.75 ± 2 .13%; 41.02 ± 0.9% versus 50.52 ± 1.49%, p < 0.05, respectively), ratio of wall/lumen thickness, as well as the wall/lumen area were significantly reduced in PAH rats at these time points following ADSCs-treatment, as compared with untreated PAH rats. In summary, ADSCs may colonize the pulmonary arteries, attenuate pulmonary arterial hypertension and ameliorate pulmonary arterial remodeling.